Anaerobic Performance and Athletic Talent in Elite Taekwondo Athletes (Revista Chilena de Rehabilitación y Actividad Física, 2025)
Introduction: It is paramount to analyze the profile and physiological needs of taekwondo athletes to optimize and enhance their sports performance. Objective: To determine the relationship between anaerobic performance variables in the rast test and athletic talent. Methodology: A quantitative research of quasi-experimental observational design with a descriptive-correlational approach was conducted. This study was carried out on Elite Taekwondo athletes affiliated with the United States Taekwondo National Governing Body (USAT) during the year 2023. Anaerobic performance was assessed using the Rast test, and athletic talent was considered as the position in the national ranking. Results: High negative relationships were identified in the variables of minimum power (-0.088) and fatigue index (-0.093), approaching significance (p